SPECTRAL AND PHOTOMETRIC RESEARCHES OF RY TAU - Ismailov, N. Z.; Adigozalzade, H. N. (Одеські астрономічні публікації, 2010)
The results of analysis of the total light curve of the classic T Tauri type star RY Tau were presented. For a time at last 48 years a brightness of the star is characterized by fluctuations with amplitude about ΔV ∼1m, with characteristic time about 300 days. Firstly we were showed, that in an interval of 1983 - 2004 in V-band light variability of the star has cyclic character with the period of 377 ±10 days. After the deepest minimum in 1995 there was some change in system therefore, since, fluctuations with amplitude about 1m are continued, the phase of the period found before this minimum showed some displacement. On the IUE archive data base we have studied a spectrum of RY Tau in the UV range. For 1979-1990 spectral observations we have measured relative intensities, FWHM (full wide at half middle) and equivalent widths of the relatively strong emission lines, as Mg II λ2800Å, S II, O I λ1334Å, C II λ1403Å, Si V λ1454Å, C IV λ1546Å, He II λ1640Å, etc. A variability of the line intensities of Mg II λ2800Å emission and absorption components with period 23.2±0.3 days was discovered. Some variability of emission line intensities from night to night was obtained.